Allostasis and the Three Essentials for Health Care: A Reflective Article. - González-Santamaríaa, Jhonatan; Jimena Lopéz-Garcíab, Claudia (Revista Médica de Risaralda)
The concept of allostasis has emerged as a key theoretical framework for understanding the body’s adaptation processes in response to environmental challenges. Building upon the evolution of the homeostasis paradigm, this article reflects on how chronic stress, resulting from unhealthy lifestyles, can trigger allostatic overload with pathophysiological consequences such as chronic inflammation, neuroendocrine dysfunction, and behavioral impairment, thereby contributing to the development of non-communicable diseases and mental disorders. In this context, regular physical activity, a healthy diet, and good sleep quality are proposed as three essential habits for health care. These behaviors act as positive modulators of allostatic load, support physiological recalibration processes, and serve as fundamental pillars in any health promotion strategy. Finally, the article advocates for the integration of these three essentials into public policies and clinical practices, recognizing their structural role in sustaining both individual and collective health.